2011
DOI: 10.2337/db11-0705
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Intra-Islet CD20 Expression May Complicate Efficacy of B-Cell–Directed Type 1 Diabetes Therapies

Abstract: OBJECTIVEConsistent with studies in NOD mice, early clinical trials addressing whether depletion of B cells by the Rituximab CD20-specific antibody provides an effective means for type 1 diabetes reversal have produced promising results. However, to improve therapeutic efficacy, additional B-cell–depleting agents, as well as attempts seeking diabetes prevention, are being considered.RESEARCH DESIGN AND METHODSAutoantibodies, including those against insulin (IAAs), are used to identify at-risk subjects for incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
97
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(119 citation statements)
references
References 43 publications
(47 reference statements)
20
97
2
Order By: Relevance
“…These results are consistent with our studies using anti-CD20 to deplete B cells in WT NOD.H2h4 mice, since anti-CD20 inhibits development of SAT, but SAT anti-CD20-treated mice develop SAT comparable to isotype-treated controls when Treg are transiently depleted . Other groups have also shown that depletion of Treg abrogates the ability of anti-CD20 to suppress diabetes (Serreze et al, 2011) and arthritis (Hamel et al, 2011). Our studies demonstrating an important role for Treg as the basis for the resistance of B cell-deficient mice to other spontaneous autoimmune diseases was demonstrated in our studies with B À/À NOD mice where transient Treg depletion resulted in development of thyroiditis, diabetes, and SS.…”
Section: B Cells and Autoantibodies In Satsupporting
confidence: 72%
“…These results are consistent with our studies using anti-CD20 to deplete B cells in WT NOD.H2h4 mice, since anti-CD20 inhibits development of SAT, but SAT anti-CD20-treated mice develop SAT comparable to isotype-treated controls when Treg are transiently depleted . Other groups have also shown that depletion of Treg abrogates the ability of anti-CD20 to suppress diabetes (Serreze et al, 2011) and arthritis (Hamel et al, 2011). Our studies demonstrating an important role for Treg as the basis for the resistance of B cell-deficient mice to other spontaneous autoimmune diseases was demonstrated in our studies with B À/À NOD mice where transient Treg depletion resulted in development of thyroiditis, diabetes, and SS.…”
Section: B Cells and Autoantibodies In Satsupporting
confidence: 72%
“…Finally, the murine CD20-specific 18B12 antibody that, like rituximab, depletes the follicular (FO) but not marginal zone subset of B cells (MZB), efficiently inhibited diabetes development in NOD mice in a likely regulatory T-celldependent manner only when treatment was initiated before IAA detection. The latter observations suggest that MZBs, which are known to be potent APCs, may well play a role in the chain of events leading to overt diabetes (Serreze et al 2011).…”
Section: Evidence For Involvement Of B-lymphocytes and Autoantibodiesmentioning
confidence: 93%
“…However, minimal work has been conducted to investigate the association between Bregs in the immune response and the occurrence of HT. Immune-mediated injury serves an important role in the pathogenesis of insulin resistance and diabetes mellitus (DM) (13,14). A previous study indicated that patients with HT had significantly increased peripheral blood CD19 + CD24 + CD27 + Bregs, and the increased percentage of CD19 + CD24 + CD27 + Bregs was correlated with fasting insulin secretion and fasting insulin resistance in patients with HT (8 In order to eliminate the effect of thyroid hormones on insulin signaling and glucose regulation in the present study, only patients with type I HT who had normal thyroid function and were not on hormone treatment were included.…”
Section: Introductionmentioning
confidence: 99%